Menjaga Kesehatan Mental Saat Pandemi Covid -19 - Firdaus, Ach. Rizal; Arya Setya Nugraha (UNIB Press, 2023)
Mental health is very important to pay attention to during the Covid-19 pandemic. Because mental health can also influence individuals in carrying out daily activities. This activity was carried out in the villages of Drajat, Paciran, Lamongan using the socialization method directly and through posters where the material was obtained from literature studies from various sources. The results of this study show that activities like this can be an alternative to increase information to the public.